Formação cultural brasileira e norte-americana na ótica de Érico Veríssimo e Vianna Moog - Carvalho, Enildo de Moura (Universidade do Vale do Rio do Sinos, 2006)
This thesis analyzes the formation of Brazil’s culture as compared to the North American culture according to the view of two Brazilian authors: Érico Veríssimo, in his books Gato preto em campo de neve and A volta do gato preto, and Vianna Moog, in his book Bandeirantes e pioneiros. Both authors belonged to the epoch-making generation of Brazilian authors who began to write in the thirties and fourties of the 20th century. Both had the opportunity to live in the United States as participants of a cultural exchange program, which made it possible for them to create the mentioned books. Some topics were predominant in the authors’ discussion, such as the comparison between the level of development and modernization in Brazil and in the States. However, both Veríssimo and Moog seem to focus their attention on the recognition of Brazil in its cultural peculiarities, in its idiosyncratic character. To do this, both authors used the discourse of literary narrative and the discourse of social science. This is why t
Keywords: comparativo; Érico Veríssimo; Estados Unidos; formação cultural; intercâmbio cultural; narrativas literárias; Vianna Moog; Brasil; Ciências Humanas